Synthesis of Calcium Carbonate Particles in Octylamine/Water Bilayer Systems - Jun Wang; William B. White; James H. Adair (KONA Powder and Particle Journal, 2014)
Calcium carbonate particles with various shapes and morphologies were prepared via precipitation in an octylamine/water self-assembly bilayer systems. Crystal structure and shape of the CaCO3 particles were determined by the water to octylamine molar ratio R of the bilayer. At R = 16.0, phase pure calcite particles with a “hopper crystal” morphology were formed, the average particle size of the hopper crystal is 10 μm with well-defined edges on the hopper faces. Decrease the R ratio to 7.2 eventually leads to the formation of 3 μm tabular CaCO3 particles which are predominated by vaterite structure. For an intermediate R of 10.8, spherical vaterite aggregates and rhombohedral calcite particles were produced. Thermal decomposition of the CaCO3 particles was observed at around 710°C. The mechanism of particle evolution in the self-assembly bilayer, particularly the formation of “hopper crystal” calcite was discussed.